2018
DOI: 10.12659/msm.906450
|View full text |Cite
|
Sign up to set email alerts
|

Lysophosphatidic Acid Promotes Expression and Activation of Matrix Metalloproteinase 9 (MMP9) in THP-1 Cells via Toll-Like Receptor 4/Nuclear Factor-κB (TLR4/NF-κB) Signaling Pathway

Abstract: BackgroundLysophosphatidic acid (LPA) is an active compound of oxidized low-density lipoprotein that serves as an endogenous TLR4 ligand. Ligand activation of TLR4 activates nuclear factor-kappaB (NF-κB) and the transcription of NF-κB-regulated inflammatory cytokines, which are involved in the development of atherosclerosis. MMP9 is a member of the MMP family and can affect plaque stability. However, the mechanism responsible for the effect of LPA on the expression and activation of MMP9 has not been fully elu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…It may well be that LPA and not LPC is responsible for the reported effects of LPC and ox-LDL on the development of atherosclerosis. [ 171 , 172 , 173 , 174 , 175 ]. Small molecule inhibitors of autotaxin, a secreted phosphodiesterase that produces LPA from LPC, and thus increasing LPC levels - are a new promising therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…It may well be that LPA and not LPC is responsible for the reported effects of LPC and ox-LDL on the development of atherosclerosis. [ 171 , 172 , 173 , 174 , 175 ]. Small molecule inhibitors of autotaxin, a secreted phosphodiesterase that produces LPA from LPC, and thus increasing LPC levels - are a new promising therapeutic option.…”
Section: Discussionmentioning
confidence: 99%
“…Little is known about whether LPP1 affects the expressions of MMPs in breast cancer. Several studies reported that LPA increases the expression of MMP-2 or MMP-9 in leukemic monocytes 32, neuroblastoma 33, hepatocellular carcinoma cells 34, and ovarian cancer cells 35. This suggests that the low LPP1 activity in cancers could increase MMP levels through the concomitant elevation in LPA signaling.…”
Section: Introductionmentioning
confidence: 99%
“…However, in cells that have not been activated by lipopolysaccharide or other methods of stimulation, baseline levels of cytokines in the media are often too low to be detected [138], [395], [397]. Therefore, while it's possible that increased proinflammatory factors in the conditioned ~ 90 ~ media from apoE2-TR mixed glial cultures, such as increased NFκB levels, is impacting MMP-9 conversion levels [353], [373], [374], they are often in such low abundance in the extracellular media under non-stimulated conditions that their potential influence is likely negligible [138], [395], [397].…”
Section: Discussionmentioning
confidence: 99%
“…Several activators of MMP-9 have been identified including MMP-2 [230], MMP-3 [231], MMP-7 [232], MMP-10 [233], MMP-13 [234], and the serine protease trypsin [235]. Increased MMP-9 activation is seen following inflammation [200], [372], for instance NF-κB signalling in human endothelial cells has been shown to affect the activation of MMP-9 [353], [373], [374]. MMP-9 is typically processed into the well-established 82-kDa active species, in some instances via an inactive 86 kDa intermediate form [231], [369], [375].…”
Section: Chapter 3: Functional Regulation Of Mmp-9 By Apoe: Conversiomentioning
confidence: 99%